TINJAUAN HUKUM PIDANA TERHADAP KEPEMILIKAN HEWAN PELIHARAAN YANG MEMBAHAYAKAN ORANG LAIN - Sarumaha, Barnabas Yusran (Universitas Harapan Medan, 2023)
Having a pet is not a problem as long as it does not violate the law and does not harm others or violate other people's rights. However, many cases occur where pets attack other people and endanger lives. This study aims to examine the legal arrangements regarding pet ownership, the implementation of rules regarding pet ownership and solutions to problems of pet ownership that endanger others. This research is a normative law research. Normative law research uses normative case studies in the form of legal behavior products, for example examining laws. This research is descriptive in nature, namely research that is explanatory in nature, and aims to obtain a complete picture of the state of the law that applies in a particular place, or regarding existing juridical symptoms, or a certain legal event that occurs in society. It was found that pets that endanger the lives of others according to criminal law are included in general criminal offenses and regulated in the Criminal Code. Pet owners can be convicted according to Article 359, Article 360 and Article 490 of the Criminal Code if their pets harm others. Cases of pet ownership endangering others often occur. Whether it is an attack or a bite that causes minor injuries to death. However, most cases are only resolved through compensation. Even though there have been several cases of pet attacks, especially dogs, which have claimed lives. Crime prevention efforts can be broadly divided into two criminal policies, namely through penal channels (criminal law) and through non-penal channels (not / outside of criminal law).